2014
DOI: 10.12691/jfnr-2-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene Action for Various Grain and Fodder Quality Traits in <i>Zea Mays</i>

Abstract: A Zea may is an important cereal crop. To nourish human and livestock, it is very important that the quality of maize grain and fodder must be higher. A study was conducted to evaluate maize accessions for grain and fodder quality traits. Results indicated that higher heritability was found for nutrient detergent fiber, fodder cellulose, fodder crude fiber, fodder crude and fodder moisture percentage while genetic advance was higher for fodder cellulose, fodder crude protein and fodder ash percentage. High sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Over 80% of total global agricultural land is rain-fed (Berzsenyi et al, 2006) thus the development of genotypes that survive better in water scarce condition is the need of hour. Phenotypic stability of the traits in maize hybrids is the best way to measure the genetic variability (Chavan et al, 2015) by overwhelming the two most common variables in field: soil heterogeneity and environment (Khorasani et al, 2011; Ali et al, 2014a,c, 2015a). Therefore, multivariate analysis (Ashmawy, 2003; El-Badawy and Mehasen, 2011) displays a better idea of the underlying latent factors and an interface between individual genotype and variable.…”
Section: Introductionmentioning
confidence: 99%
“…Over 80% of total global agricultural land is rain-fed (Berzsenyi et al, 2006) thus the development of genotypes that survive better in water scarce condition is the need of hour. Phenotypic stability of the traits in maize hybrids is the best way to measure the genetic variability (Chavan et al, 2015) by overwhelming the two most common variables in field: soil heterogeneity and environment (Khorasani et al, 2011; Ali et al, 2014a,c, 2015a). Therefore, multivariate analysis (Ashmawy, 2003; El-Badawy and Mehasen, 2011) displays a better idea of the underlying latent factors and an interface between individual genotype and variable.…”
Section: Introductionmentioning
confidence: 99%
“…Maize is an important cereal crop that is grown as food for human and feed for livestock. Its grain constitutes about 9.7396 % grain protein, 4.85% grain oil, 9.4392% grain crude fibre, 71.966% grain starch, 11.77% embryo while fodder contains 22.988% acid detergent fibre, 51.696% neutral detergent fibre, 28.797% fodder cellulose, 40.178% fodder dry matter, 26.845% fodder crude fibre, 10.353% fodder crude protein and 9.095% fodder moisture [1][2]. Nitrogen is the most important nutritive element for the production of maize.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation of seedling traits indicated that the shoot and root length and their weights may be utilized for the selection of better-yielding maize genotypes under salt stress conditions. The higher shoot and root length caused to increase photosynthetic rate in leaves and led to the accumulation of organic matters in the seedling body, due to which the growth and development of maize seedlings improved even under salt stress conditions [69,74,75,76].…”
Section: Discussionmentioning
confidence: 99%